Contribuição da tutoria no ensino-aprendizagem dos professores cursistas do PROFORMAÇÃO - Oliveira, Alice Virgínia Brito de (2008)
The EAD has been developed through ICT also mediated by tutoring. This survey aimed to examine the practice of teaching tutors in the teaching-learning at a distance within the Programme for Training of Teachers on Strike-Proformação, studying public policy of EAD for teacher training; examine the conceptions of the teaching program with emphasis on the role of guardian. The contribution of mentoring teachers in learning for teachers was central problem and that is how this influence and profile of these tutors. The research made by the case study of AGF / Arapiraca-AL. The data collection took place through the use of questionnaires, conducting an interview and observation presence at meetings of tutors. The analysis of official documents and external assessments conducted in the present positive data, but research focuses on the contributions the field of mentoring for the practice of teachers teaching teachers in the process of interactions, construction of identities, conflict and cognitive learning is important for perception of the elements guiding the problems investigada.Como results, the data show a great level of satisfaction of those involved, but also presenting the points that hamper the process of learning for teachers teaching teachers.